Clutch Abandoning Parasitised Yellow Warblers Have Increased Circulating Corticosterone With No Effect of Past Corticosterone or Differences in Egg Maculation Characteristics - Turcotte-van de Rydt, Antoine V.; Petalas, Christina; Sblendorio, Joanna M.; Pearl, Christopher A.; Gill, Sharon A.; Guigueno, Mélanie F. (Frontiers in Ecology and Evolution, 2022)
Parental care can be costly to parents’ fitness. As such, abandonment of the current reproductive attempt may benefit potential future opportunities, maximizing lifetime reproductive success. Obligate brood parasitism, a reproductive strategy in which parasites lay their eggs in the nests of other species and rely solely on them to raise the parasitic young, is an ideal system to study brood abandonment. Some parasitized host species have evolved anti-parasitic defenses, notably clutch abandonment (egg burial and nest desertion), that may mitigate negative consequences of parasitism. Abandonment of clutches due to parasitism is not unlike abandonment of reproduction in times of stress, suggesting that host responses to parasitism could be triggered at least partly by elevated stress hormones that mediate individual decisions. Yet, the mechanistic basis for clutch abandonment remains unclear. Here, we experimentally parasitized clutches of yellow warblers (Setophaga petechia), a common host of the brown-headed cowbird (Molothrus ater), with model cowbird eggs to examine whether host circulating corticosterone (CORT) differed among females that accepted parasitic eggs or rejected them through clutch abandonment. We also assessed whether feather CORT, a measure of past corticosterone exposure, differed between accepters and abandoners. Finally, we investigated whether egg visual signals, specifically differences in maculation characteristics between model cowbird and host eggs, predicted abandonment of experimentally parasitized clutches. Circulating CORT was higher in females who abandoned their parasitized clutches, but not in those who accepted, relative to controls with no egg addition. Past stress and differences in maculation characteristics did not predict whether individuals accepted or abandoned experimentally parasitized clutches. Moreover, differences in maculation characteristics between the host and model cowbird eggs did not predict CORT levels or nest abandonment. Thus, parasitism with subsequent clutch abandonment may be associated with elevated circulating CORT, but neither past stress nor differences in maculation characteristics influenced abandonment. The combination of these results contributes to our understanding of the roles of corticosterone and egg visual signals in the context of clutch abandonment in brood parasitism specifically, and of parental care more broadly.